Impact of Social Media on Shoppers - Agarwal, Varsha (International Journal of Scientific Development and Research, 2022)
‘Content is fire. Social media is gasoline’, a quote by Jay Baer is more relevant than ever in today's modern day and age. This is a world which is guided by the new generations and the internet has taken the world up by a storm. Since the majority of businesses are moving toward an online orientation, they must offer and sell things via various online channels. The goal of the study is to shed light on how social media influences various phases of consumers' purchase decision-making and how it differs from mass media in this regard. It also aims to investigate the relationship between hedonic shopping value and attitudes toward product messages on social media platforms. The decision-making process for consumers has been profoundly altered by social media, and during the past ten years, a more nuanced understanding of how customers interact with brands has arisen. Social media, as a communication tool, promotes consumer feedback, which has a strong psychological impact and thus leads to shopping bias.
ISME